Decision-Making Framework for Medical Equipment Maintenance and Replacement in Private Hospitals - Salim, Siti Hajar; Salim, Siti Aisyah (International Journal of Sustainable Construction Engineering and Technology, 2023)
The process for medical equipment maintenance and replacement in hospitals is a challenging and demanding procedure. Further, the topic of making decisions to maintain or replace or upgrade medical equipment has been debated for a long time since errors equipment maintenance will increase equipment failure at undesirable times; or if early equipment replacement will result in high investment costs and premature disposal. Therefore, standard operating procedures or guidelines need to be in place to help healthcare facilities conduct a more organized and planned maintenance and replacement process. Many hospitals may already have established replacement guidelines or have implemented asset monitoring systems for this purpose. However, the effectiveness of this system has not yet been systematically evaluated. Several studies have been conducted on the same research topic, but most of the findings emphasize the replacement method rather than the criteria that contributed to the decision. Criteria for replacing medical equipment play an important role in ensuring that the equipment can be used cost-effectively. Thus, this research aims to identify important criteria that need to be considered for medical equipment maintenance and replacement focusing on private hospitals. This research was conducted in three phases: (1) a structured literature review; (2) semi-structured interviews with eleven (11) healthcare experts; and (3) a pairwise comparison survey with 50 biomedical engineers. A decision-making framework was developed based on the findings of these three research phases. The framework developed will provide guidelines for practitioners and academics to understand and make better decisions for medical equipment maintenance and replacement in the context of private hospitals.